2016
DOI: 10.1016/j.cbpa.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

How PEGylation influences protein conformational stability

Abstract: PEGylation is an important strategy for enhancing the pharmacokinetic properties of protein therapeutics. The development of chemoselective side-chain modification reactions has enabled researchers to PEGylate proteins with high selectivity at defined locations. However, aside from avoiding active sites and binding interfaces, there are few guidelines for the selection of optimal PEGylation sites. Because conformational stability is intimately related to the ability of a protein to avoid proteolysis, aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 58 publications
1
83
0
Order By: Relevance
“…In this work, a β-sheet conformation was observed for DDAAAAAA and DDVVVVVV peptides, which was not affected after conjugation with PEG. Actually, the effect of PEGylation on conformational stability of proteins or peptides is not well clarified 26 . In some studies, no effect was observed on the secondary structure of epta-or octapeptides after PEGylation 27 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, a β-sheet conformation was observed for DDAAAAAA and DDVVVVVV peptides, which was not affected after conjugation with PEG. Actually, the effect of PEGylation on conformational stability of proteins or peptides is not well clarified 26 . In some studies, no effect was observed on the secondary structure of epta-or octapeptides after PEGylation 27 .…”
Section: Resultsmentioning
confidence: 99%
“…due to proteolytic degradation 26 . In this study, therefore, we adopted a different approach to produce biobetter glucarpidases, which should both reduce the potential for antibodies production and also protect the protein against endogenous proteases.…”
Section: Discussionmentioning
confidence: 99%
“…In a Fab, both VH/VL and CH/CL interactions contribute to the functional stability of the antibody fragment and potentially to the in vivo toxin neutralization capacity as suggested previously [66]. In addition, one can consider site-specific PEGylation of scFvs for enhancing the pharmacokinetic properties, the conformational stability, protection from proteolysis and immunogenicity [67]. Altogether, these findings represent a proof of concept on humanized mouse antibodies specific to animal toxins, encouraging the optimized production of molecules for in vivo assessment.…”
Section: Discussionmentioning
confidence: 99%